Racial formation in the reporting of Canadian immigration - Carol, Schick (Adult Education Research Conference, 1995)
Using Howard Winant’s racial formation theory, I analyze the coverage of news stories and editorials in Canada'’ national newspaper in light of recent changes to Canadian immigration policy. Discourse analysis reveals the structural and racial significance of immigration to the racialization of Canadian identity.